Transforming economics towards tackling teachers' challenges in teaching economics: A case of selected schools in buffalo city metropolitan South Africa - Adu, Emmanuel Olusola (Nurture, 2023)
Introduction/Purpose: Economics is a dynamic subject whose students use the contents to address real-life problems. Therefore, this paper examines the transformation of economics to tackle teachers’ challenges in the teaching of economics. Design/Methodology/Approach: This paper used a qualitative research technique to collect information from teachers based on a phenomenological research design. A purposive sampling technique was used to select 12 teachers of economics in 6 selected schools in Buffalo City. A semi-structured interview was used to elicit information from the respondents and the data were analysed using a thematic approach. Findings: The study identifies certain notable issues including imprecise economics curriculum materials and learners' inability to demonstrate interest due to various statistics and data components of the subject. Teachers' participation in professional development activities such as seminars, in-service training and workshops for knowledge updates is one of the solutions offered to overcome these difficulties. Limitation: This paper uses only 12 economics teachers from Buffalo City metropolitan municipality. Larger samples can be used in another municipality. A quantitative approach can be used to accommodate representative samples. Practical Implications: Teachers are expected to be at the forefront of disseminating the contents of the subject appropriately because a teacher can only give what he or she has. Teachers should be proactive and current with the recent developments in the nation and be technologically compliant. Contribution to the Literature: This paper contributes to the literature by highlighting practical solutions to the challenges teachers face during the teaching of economics.